Case Study on Physical Education and Sport in Naples, Italy - Di Tore , P. A; Raiola , G. (Richtmann Publishing, 2012)
In 2009 Minister of Education University and Research (MIUR) of Italy enacted the Guidelines of physical education and sport to improve the sport activity into the school through the sport school association and gives, for this aim, only 33% of amount of economical resources allocated in the previous years for extra activity of physical education. Approach: From a case study to compare data between 2 years of a sample of 10 schools of Naples, 6 schools decreased sports activity, 4 schools slightly increased and only one school increased significantly adding own economical resources. Furthermore, this school also deliberated a collaboration with sport association as new Guidelines suggested. The aim of this study is to investigate the process adopted by the school. Method is case study to describe the process. Results and Conclusion: All 10 schools confirm the past sport activities in different forms with several percentages among the schools. The decrease of number of students is significant and generally distributed. Seven schools utilized only the economical ministerial resource and only 2 schools utilized economical ministerial resources and a few own economical resources. The datum of only one school adding own economical resource in congruent amount means that just the 10% of schools understand the spirit of change according to the new Guidelines of Physical Education and Sport. The study suggests to start an investigation on public sport education service offered by school and by sport association and to establish a specific committee to investigate every aspect of this phenomenon.